2006
DOI: 10.1021/ol0608092
|View full text |Cite
|
Sign up to set email alerts
|

Verpacamides A−D, a Sequence of C11N5Diketopiperazines Relating Cyclo(Pro-Pro) to Cyclo(Pro-Arg), from the Marine SpongeAxinellavaceleti: Possible Biogenetic Precursors of Pyrrole-2-aminoimidazole Alkaloids

Abstract: [reaction: see text] Four C(11)N(5) diketopiperazine metabolites named verpacamides A (6), B (7), C (8), and D (9) consisting of a proline-arginine dipeptide skeleton have been isolated from the marine sponge Axinella vaceleti. Verpacamides A-D are a sequence of metabolites showing the transformation of proline and arginine into the oxidized guanidinyl-cyclo(Pro-Pro) 8 and 9. Compounds 6-9 are structurally and chemically related to C(11)N(5) pyrrole-2-aminoimidazole metabolites also isolated from the Axinellid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…Verpacamides A -D (121 -124, resp. ), isolated from Axinella vaceleti (Mediterranean Sea), are considered to represent possible intermediates in an alternative biogenetic pathway to pyrrole-2-aminoimidazole alkaloids such as oroidin [92]. Verpacamide A is known as a synthetic product [92].…”
mentioning
confidence: 99%
“…Verpacamides A -D (121 -124, resp. ), isolated from Axinella vaceleti (Mediterranean Sea), are considered to represent possible intermediates in an alternative biogenetic pathway to pyrrole-2-aminoimidazole alkaloids such as oroidin [92]. Verpacamide A is known as a synthetic product [92].…”
mentioning
confidence: 99%
“…More recently Al-Mourabit and coworkers proposed a biogenetic pathway [14] for P-2-AI early precursors from proline and related arginine. This proposal (Scheme 7.4) was based on the isolation of verpacamides A (24) and C (25) sponge Axinella vaceletti.…”
Section: Proposed Biogenetic Hypothesis For Clathrodin (1) and Relatementioning
confidence: 99%
“…Al-Mourabit's synthesis of oroidin (3) based on the biogenetic proposal for pyraxinine(14) and dibromoagelaspongine(6). Reagents and conditions: Scheme 7 10.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] In the NOESY spectrum, an NOE correlation observed between H-11 and H-16 indicated that the hydroxyl group at C-16 is β-oriented (Figure 2). Furthermore, H-11 and H-16 did not give any NOE correlation with the methoxy group, suggesting that the orientation of the methoxy group at C-17 is β, which is opposite to that of the methoxy group of verpacamide D. 8 The observation of unusual upfield-shifted proton chemical shift of the methoxy group could be rationalized by the presence of coplanar C-18 carbonyl group. Molecular models of compound 3 indicated that the methoxy protons are positioned at shielding zone of the carbonyl group, thereby resonated at relatively upfield region compared to usual methoxy protons.…”
mentioning
confidence: 91%
“…The 1 H and 13 C NMR data of the diketopiperazine moiety of 3 were found to be similar with those of the similar partial structure, verpacamide D, except for the chemical shift value of the methoxy group and C-17. 8 This difference might be due to the different configurations of the methoxy groups of these two compounds, so an NOESY experiment was carried out to determine the relative configuration of 3. As all the diketopiperazine alkaloids isolated from the fungi Penecillium showed the configuration at C-11 to be S, therefore the orientation of proton at C-11 of 3 could be assumed as α based on the biogenetic considerations.…”
mentioning
confidence: 99%